Ulisses e Narciso: as faces da alma humana através do discurso mítico nas Enéadas de Plotino - Santos, Vanessa Alves de Lacerda (2012)
This dissertation, witch studies the myth in Plotinus, attempts to set an approach to the comprehension of the mythic discourse as image related to the ethical process in the Enneads. In order to achieve it, the analysis of the mythic narrative will be employed in the philosophical context that has as a starting point a revisit of the platonic poetic conception. As central questions the notable mythological figures of Narcissus and Ulysses will be utilized to put into context the notion of the Plotinian soul and its endeavor of returning to the originary unity. Therefore, by following the course of both figures in their respective narratives, it conceives a possible relation of ascension and fall of the soul. The first part of this study intends to show Plato s interpretation on the myth and Plotinus standpoint in regard to it. Moreover, it observes Plato s criticism on poetry in the context of the Greek Paideia and the notion of the myth as image of the henological structure in Plotinus, who perceives in the myth its exemplifying nature. The second part attempts to structure Plotinus philosophy, contrasting Henology and Ontology, therefore exposing the three hypostases and the comprehension of the intelligible. The third part endeavors to display the sense of the myth, the idea of the myth as image in Plotinus and the roles of the mythical figures in the Enneads